0024 An Antidote To Toxicology Training. (1st November 2014) - Stead, Richard; Murray, Sam; Henry, Marc; Dimmock, Val; Mulchandani, Haresh; Buckley, Anna; Watson, David
Abstract : Background/context: Poisoning accounts for 140, 000 hospital admission each year and in 2011 there were 2652 drug related deaths in England and Wales. 1, 2 The National Poisons Information Service have highlighted an opportunity to improve the management of severely poisoned patients in hospital. 1 Toxicology forms part of the curriculum in Emergency, Acute Medicine and Intensive Care. Despite this, we have identified a lack of specialist training focused in this area. Patients present acutely following poisoning with signs and symptoms that can be difficult to interpret. Their management requires specialist knowledge and skills in clinical decision making, communication and multidisciplinary teamworking. We believe high-fidelity simulation offers an effective environment to deliver toxicology training. Method: A multi-professional high-fidelity simulation day was designed with five scenarios mapped to curriculum objectives. Each scenario was followed by a de-brief and a short presentation about the toxidrome encountered. A post-course feedback questionaire was collected. An anonymised post-course 10 question MCQ paper on toxicology was completed by the doctors. The MCQ paper was also given to a control group of 10 A&E doctors of similar experience who had not attended the day. Results: The course was attended by 5 doctors (FY2-ST4) and 4 A&E nurses. All the candidates (100%) found the content and presentation of the information to be extremely useful. They found it 'beneficial and relevant', 'more applicable than reading a textbook', 'useful working as a team' and would 'recommend it to others'. Following the training day, the candidates scored on average 13% higher on the MCQ paper compared to the control group. Conclusion: Simulation is an effective way of training healthcare professionals in the diagnosis and treatment of patients with acute poisoning. Having received excellent feedback and demonstrated it to be a beneficial learning tool, we plan to run further courses in the future. References: National Poisons Information Service Report 2012/13: http://www.hpa.org.uk/webc/HPAwebFile/HPAweb_C/1317139808601 Office of National Statistics: Deaths related to Drug Poisoning in England and Wales, 2011 Release: http://www.ons.gov.uk/ons/publications/re-reference-tables.html?edition=tcm%3A77-266060